Cortisol changes in healthy children and adolescents during the COVID-19 pandemic. (2nd January 2022) - Fung, Madison H.; Taylor, Brittany K.; Embury, Christine M.; Spooner, Rachel K.; Johnson, Hallie J.; Willett, Madelyn P.; Frenzel, Michaela R.; Badura-Brack, Amy S.; White, Stuart F.; Wilson, Tony W.
Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic has caused massive disruptions to daily life in the United States, closing schools and businesses and increasing physical and social isolation, leading to deteriorations in mental health and well-being in people of all ages. Many studies have linked chronic stress with long-term changes in cortisol secretion, which has been implicated in many stress-related physical and mental health problems that commonly emerge in adolescence. However, the physiological consequences of the pandemic in youth remain understudied. Using hair cortisol concentrations (HCC), we quantified average longitudinal changes in cortisol secretion across a four-month period capturing before, during, and after the transition to pandemic-lockdown conditions in a sample of healthy youth ( n = 49). Longitudinal changes in HCC were analyzed using linear mixed-effects models. Perceived levels of pandemic-related stress were measured and compared to the physiological changes in HCC. In children and adolescents, cortisol levels significantly increased across the course of the pandemic. These youth reported a multitude of stressors during this time, although changes in HCC were not associated with self-reported levels of COVID-19-related distress. We provide evidence that youth are experiencing significant physiological changes in cortisol activity across the COVID-19 pandemic, yet these biological responses are not associated with perceived stress levels. Youth may be especially vulnerable to the deleterious impacts of chronic cortisol exposure due to their current status in the sensitive periods for development, and the incongruency between biological and psychological stress responses may further complicate these developmental problems.